A Time to Pause and Reflect: When a Patient with Autoimmune Hepatitis Stops Responding to Corticosteroids. (25th December 2016) - Tsang, Lewis; Fadia, Mitali; Chitturi, Shivakumar
Abstract : Drug-induced liver injury (DILI) with features of autoimmunity (AI) is a challenging diagnosis to make particularly due to its apparent corticosteroid responsiveness. We present the case of a 74-year-old woman who presented with a 2-week history of jaundice and fatigue. She was initially diagnosed with autoimmune hepatitis (AIH) based on biochemical and histological characteristics and prompt response with budesonide but a biochemical relapse occurred soon after inadvertent rechallenge with irbesartan, a drug that she had discontinued prior to her presentation but was not initially considered to be a cause of her symptoms.